Right TKR Patients Treated with Enhanced Pain and Rehabilitation Protocols Can Drive at 2 Weeks - Dalury, David F.; Chapman, Danielle M. (The Journal of Knee Surgery, 2019)
An important milestone in the recovery following total knee replacement (TKR) is the ability to return to driving. With advances in pain control and the widespread introduction of rapid rehab programs, we hypothesized that the ability to drive would also return sooner than had been traditionally observed. In our group of consecutive right TKR patients, using a driving simulator, we showed that at the 2-week mark, 36 of the 40 patients tested had returned to their preoperative driving capabilities and the other 4 had reached baseline at 3 weeks. While the eventual decision to return to driving is complex and dependent on many factors, we conclude that one of the benefits of enhanced pain and rehab protocols is that patients undergoing right TKR can return to driving in most instances at the 2-week mark rather than the traditional 6-week mark.
Keywords: total knee replacement; brake reaction time; return to driving